Kuwait : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Securities Regulation, Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2004)
This Financial System Stability Assessment on Kuwait reviews the macroeconomic environment and gives an overview of the financial system. Financial stability has been effectively supported by prudent fiscal and monetary policies. The banking sector appears sound and is well regulated and supervised. Sensitivity to market risk is limited owing to the short-maturity structure of interest bearing instruments, while exchange rate risk has been contained by strict enforcement of prudential requirements. Equity prices have once again increased markedly and reached new record highs.